Strategic research on RF and microwave - Ng, Geok Ing (2008)
An introduction to the background, objectives and achievements of the project is given in chapter 1. This is followed by a detailed description of the microwave load pull measurement system in chapter 2. A brief introduction of the load pull concept is made. This is followed by a detailed characterization of the load pull system. With this set-up, several AlGaAs/InGaAs pHEMT and HBT devices fabricated at NTU have been measured to evaluate their power performance. The 6X100 // m PHEMT showed power density in excess of 500 mW/mm with a 16 dB gain at 5GHz when biased for maximum power and PAE of 61% under class AB operation at 3.5 V Vds. In the low voltage application this power density is shown to be comparable to state-of-the art performance The 3X15 //m2 self-aligned HBT demonstrated power density in excess of 2.5mW/um2 at 2.5GHz with PAE in excess of 67 % without harmonic tuning. These results are also comparable to existing technologies elsewhere. A large emitter area 160 //m2 HBT also demonstrated power in excess of 500 mW (power density of 3.3 mw//i m2) at 2.5 GHz.